Aktivitas Mukolitik Kombinasi Ekstrak Etanol Daun Kemangi dan Ekstrak Etanol Daun Sirih Merah - Neng Fisheri Kurniati; Deden Winda Suwandi; Safira Yuniati (Universitas Indonesia, 2018)
Cough is a protective physiological mechanism that is useful for removing and clearing the respitory tract from sputum and foreign particles that can cause infection. Treatments on cough disorders using synthetic drugs are known to cause side effects. Therefore, it is important to develop new alternative cough drug derived from medicinal plant which has less side effects. Basil leaves (Ocimum sanctum L.) and red betel leaves (Piper cocatum Ruiz and Pav) have been used traditionally to treat cough. Thus, the purpose of this study was to determine the mucolytic activity and the effective concentration of combination of basil and red betel leaves ethanol extract. The mucolytic activity was performed by measuring the decrease of viscosity of artificial sputum from the cow intestinal mucosa upon extracts treatment with various concentrations. Results shows that ethanol extract of basil leaves or ethanol extract of red betel leaves can reduce viscosity of artificial sputum at dose of 0.5% each. Moreover, combination of these extracts synergistically decreases the viscosity. Combination of ethanol extract of basil leaves and red betel can be an alternative medicine for cough treatment.